Design and Application of Electronic Tracking Control Systems (ETCS) to Improve Vehicle Safety - Roni Muhammad Susanto; Taufik Nurrochman; Suroto Munahar; Anwar Ilmar Ramadhan (Automotive Experiences, 2019)
Fuel and chemical cargo are essential tools for national security. There is the potential for fire and environmental pollution when occurring an accident such as a collision or overturning. On the other hand, cases of cargo theft are also reported frequently. Currently, preventive efforts are carried out by attaching warnings to the vehicle body with stickers, but it is a passive method. Therefore, this article presents a design and application for monitoring vehicles in real-time with Electronic Tracking Control Systems (ETCS). If the vehicle speed is more than 60 km/hour, ETCS will send an SMS to the vehicle owner about the speed and location of the vehicle being monitored. With ETCS, vehicle accidents and misuse can be minimized by quick monitoring and communication between the owner and the driver.